Pengaruh Penerapan Kurikulum Merdeka Belajar Terhadap Prestasi Akademik: Studi Kasus Mahasiswa PBA UIN Mataram - Fahmi, Izul; Suparmanto, Suparmanto; Swala, Meta; Walid, Muhammad; Hadi Anggara, Wiryan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The curriculum is a crucial element in the implementation of learning in a school. The curriculum plays a role in determining the direction, purpose, or goals of national education. Without a curriculum, any education system will not be well-executed, and educational goals cannot be optimally achieved. So important is the curriculum to education that the government has made amendments to it ten times. Since 2020 until now, the Ministry of Education and Culture has issued a policy in the form of a curriculum change from the 2013 curriculum to the